Paste-like dental material and glass composition therefor and preparation method thereof
By combining alumina and yttrium oxide in dental ceramics to adjust their mass ratio, the problem of mismatch between the tribological properties of dental ceramics and human enamel is solved, and a high wear resistance and translucent dental material is achieved, suitable for oral restoration.
Patent Information
- Application Number
- CN202411949234.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
AI Technical Summary
The tribological properties of existing dental ceramics do not match the tribological properties of human tooth enamel, resulting in excessive wear and tear of dental restorations during chewing, causing oral diseases.
By combining alumina and yttrium oxide in paste-like dental glass compositions, the mass ratio is adjusted, and the wear resistance of the material is significantly improved, and it is ensured to be translucent before and after sintering, avoiding graying or blackening.
It achieves the tribological matching of dental ceramics and human enamel, significantly improves the wear resistance and hardness of the material, and ensures the transparency and stability of the material, which is suitable for clinical needs of oral restoration.
Smart Images

Figure QLYQS_1 
Figure BDA0005214454250000051 
Figure BDA0005214454250000191
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of tooth restoration, in particular to a paste-like dental material and a glass composition thereof and a preparation method thereof. Background Art
[0002] Teeth are organs that directly perform chewing functions in the human body and are closely related to pronunciation, speech, and facial coordination and beauty. Human natural teeth are mainly composed of three hard tissues: enamel, dentin, and cementum, and dental pulp. The dental pulp is the only soft tissue in natural teeth. It is located in the pulp cavity in the center of the tooth. Its main function is to form dentin and has the ability of nutrition, sensation, and defense. The crown composed of enamel and dentin is the main area where natural teeth in the human body undergo chewing wear. The enamel on the outer layer of the crown is about 2mm thick, milky white, with a certain degree of transparency and a dense structure. It is the most mineralized and hardest tissue in the human body and has a greater resistance to chewing wear. The dentin on the inner layer of the crown is yellow-white, with a high organic content and low hardness. In addition, there are dentin tubules with a diameter of about 0.9 to 2.5μm distributed inside. It has good permeability and allows tissue fluid and liquid media in the local environment of the tooth to pass through. Compared with the dense and hard enamel, dentin has a certain elasticity, which can properly buffer the bite force acting on the enamel surface and prevent the enamel from catastrophic fragmentation and failure during chewing. However, the dentin structure is loose and porous, and has poor wear resistance. Once the enamel is excessively worn and the dentin is exposed on the occlusal surface, it will cause a variety of oral diseases such as tooth sensitivity, pulpitis, periodontitis, and chewing dysfunction. Therefore, in terms of the chewing function of natural teeth in the human body, the wear resistance of enamel is crucial.
[0003] Healthy human tooth enamel has excellent wear resistance, and the average annual wear depth in the oral cavity is 15 to 29 μm. Mature human tooth enamel cannot regenerate. Once disease, trauma and other factors cause enamel defects, dental materials must be used in time to reconstruct the tooth's anatomical morphology and physiological function. Dental ceramics are widely used in oral restoration clinics, but their tribological properties are far from those of human tooth enamel, which can easily lead to excessive wear of the opposing natural teeth. Therefore, there is an urgent clinical need to achieve a match between the tribological properties of dental ceramics and human tooth enamel. The development of highly wear-resistant dental paste-like materials can solve the problem of mismatch in tribological properties between ceramic restorations and natural human teeth.
[0004] Among the disclosed paste-like dental glass compositions, CN118252758A discloses a dental ceramic paste containing inorganic salts and a preparation method thereof, wherein the raw materials are a substrate glass with an average particle size D50 of 1 to 20 μm, a hydrophobized microparticle silica with an average primary particle size of 1 to 50 nm, an organic solvent with a boiling point of 100 to 300°C, and an inorganic salt. The dental ceramic paste hardly produces carbonization or bubbles during firing even when it contains organic components. This solution adds alumina, and the ability of alumina to improve wear resistance and hardness is lower than that of nano alumina, so the wear resistance of the paste is average. Because of the addition of hydrophobized microparticle silica, the transparency of the paste is suppressed, and the transparency is poor, which limits the application of the material.
[0005] CN116546939A discloses a paste-like dental glass composition, which can accurately adjust the color tone without discoloring to black or gray after calcination, and the dripping of the paste is suppressed, and the workability is good. In addition, the composition does not substantially contain an organic compound having more than 3 hydroxyl groups in the molecule, the organic solvent has less than 2 hydroxyl groups in the molecule, and the viscosity at 20°C is less than 2500mPa·s. On the one hand, the dental ceramic paste does not contain raw materials that improve wear resistance, and the wear resistance is general. On the other hand, the liquid part of the paste does not contain additives such as inorganic salts, and long-term stability is difficult to maintain. With the change of time, the paste will experience solid-liquid separation, thereby affecting the state of the paste and the sintering effect.
[0006] Therefore, it is necessary to develop a paste-like dental glass composition that is highly wear-resistant (wear resistance coefficient ≤ 0.50), has no bubbles after calcination, does not turn gray or black, and is translucent before and after sintering, so as to meet the clinical needs of oral restoration and achieve the need to match the tribological properties of dental ceramics with human enamel. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides a paste-like dental material and a glass composition used therefor and a preparation method thereof. By compounding aluminum oxide and yttrium oxide, the wear resistance of the paste-like dental material can be significantly improved, and the paste-like dental material is translucent before and after sintering, and will not turn gray or black, and has broad application prospects.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a paste-like dental basic glass powder, wherein the basic glass powder comprises aluminum oxide and yttrium oxide;
[0010] Wherein, the mass ratio of aluminum oxide to yttrium oxide is 2.75-44:1.
[0011] The present invention can significantly adjust the wear resistance of the paste-like dental material by adjusting the ratio of aluminum oxide and yttrium oxide, and the wear resistance mainly affects the wear of the tooth enamel surface after sintering. The present invention can further improve the wear resistance and hardness by synergizing aluminum oxide and yttrium oxide and strictly controlling the ratio of the two within the above range, and at the same time ensure the translucent state before and after sintering.
[0012] Specifically, the mass ratio of aluminum oxide to yttrium oxide is 2.75 to 44:1, for example, it can be 2.75:1, 7:1, 10:1, 13:1, 15:1, 18:1, 20:1, 25:1, 30:1, 30:1, 35:1, 40:1, 43:1 or 44:1, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0013] Preferably, the alumina raw material and the yttrium oxide raw material in the basic glass powder are independently nano alumina and nano yttrium oxide.
[0014] It is worth noting that the present invention limits the particle size of the alumina raw material in the basic glass powder to the nanometer level. The nanometer-level alumina can enter the silicon-oxygen crystal grid, connect the broken silicon-oxygen grid, make the glaze lattice after sintering more compact, and inhibit phase separation, so that the structure is more stable, the thermal stability is higher, and the mechanical properties are better. Nano-alumina can also improve the viscosity of SiO2, making the formed glaze surface smoother, more uniform, and more bonded to the restoration matrix. The hardness and fracture toughness of the ceramic material with nano-yttrium oxide added are stronger than those of the ceramic material with conventional yttrium oxide added. The grain size of the nano-level powder is very small, the specific surface area is relatively large, the sintering is more dense, and it has the characteristics of high temperature resistance, high wear resistance and high hardness. Because the grain size of the nano-level powder is very small and the specific surface area is relatively large, the sintering power is greatly improved, the surface diffusion rate is increased, and the sintering activation energy is reduced. The reduction in the pore size between the particles leads to a shortened diffusion path, and these factors accelerate the sintering rate. This significantly reduces the sintering densification temperature and shortens the time required for sintering densification, greatly reducing energy consumption and costs for industrial production.
[0015] Preferably, the particle size of the alumina raw material is 1 to 100 nm, for example, it can be 1 nm, 2 nm, 3 nm, 4 nm, 10 nm, 12 nm, 15 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0016] Preferably, the particle size of the yttrium oxide raw material is 1 to 100 nm, for example, it can be 1 nm, 2 nm, 3 nm, 4 nm, 10 nm, 12 nm, 15 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0017] Preferably, the basic glass powder further comprises B2O3, CaO and alkali metal oxides.
[0018] Preferably, the composition of the basic glass powder is as follows, measured by mass fraction:
[0019]
[0020] Specifically, the content of aluminum oxide in the basic glass powder is 5.5-11%, for example, it can be 5.5%, 6.2%, 6.8%, 7.4%, 8%, 8.6%, 9.2%, 9.8%, 10.4% or 11%, etc., but is not limited to the listed values, and other values not listed in this range are also applicable. The content of yttrium oxide in the basic glass powder is 0.25-2%, for example, it can be 0.25%, 0.46%, 0.68%, 0.9%, 1.12%, 1.34%, 1.56%, 1.78% or 2%, etc., but is not limited to the listed values, and other values not listed in this range are also applicable.
[0021] Preferably, the content of SiO2 in the base glass powder is 40-60% by mass, for example, it can be 40%, 43%, 45%, 47%, 49%, 52%, 54%, 56%, 58% or 60%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0022] Preferably, the content of B2O3 in the base glass powder is 6 to 15% by mass, for example, it can be 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0023] Preferably, the CaO content in the base glass powder is 2-5% by mass, for example, it can be 2%, 2.4%, 2.7%, 3%, 3.4%, 3.7%, 4%, 4.4%, 4.7% or 5%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0024] In the present invention, calcium oxide can adjust the chemical stability of the glass composition, and the calcium oxide produced by the decomposition of calcium oxide can react with other components in the glass composition. For example, it can react with silicon dioxide (SiO2) to form compounds such as calcium silicate (CaSiO3). These compounds can be filled in the structure of the glass composition to improve the chemical stability of the glass composition. Good chemical stability enables the glass composition to resist chemical erosion when it contacts chemical substances, such as acids and alkalis. Calcium oxide can improve mechanical properties. Since the addition of calcium oxide promotes the uniform growth of crystals, the crystal structure of the glass composition is more compact, and this compact crystal structure helps to improve the hardness and strength of the glass composition.
[0025] Preferably, the content of alkali metal oxide in the base glass powder is 10-25% by mass, for example, it can be 10%, 11.9%, 12.8%, 14.7%, 15%, 15.9%, 16.8%, 17.7%, 18.6%, 19.5%, 20.4%, 21.3%, 22.2% or 24%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0026] Preferably, the content of Na2O in the base glass powder is 3-14% by mass, for example, it can be 3%, 4.4%, 5.9%, 6.7%, 8%, 8.5%, 8.9%, 9.4%, 9.8%, 10.3%, 10.7%, 11.2%, 12.6% or 14%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0027] Preferably, the content of K2O in the base glass powder is 4-10% by mass, for example, it can be 4%, 5.3%, 6.5%, 6.7%, 6.9%, 7.2%, 7.4%, 7.6%, 7.8%, 8%, 8.2%, 8.3%, 8.4%, 9.5%, 9.8% or 10%, etc., but is not limited to the listed values, and other values not listed in the range are also applicable.
[0028] Preferably, the content of Li2O in the base glass powder is 0.5-3% by mass, for example, it can be 0.5%, 1%, 1.3%, 1.5%, 1.7%, 1.9%, 2.2%, 2.4%, 2.6%, 2.8% or 3%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0029] Preferably, the alkali metal oxide comprises a combination of Na2O, K2O and Li2O.
[0030] It is worth noting that the composition of the basic components of the present invention is also critical. It is precisely because of the addition of nano-alumina and nano-yttrium oxide to the basic raw materials that the performance of the ceramic material can be greatly improved. Specifically, the higher the content of high-melting-point glass-forming oxides, the higher the sintering temperature and the slower the sintering rate. The melting temperature of B2O3 is lower, and it is the main component for lowering the sintering temperature. However, if only B2O3 is used to lower the sintering temperature, the stability, mechanical strength, bonding strength with the restoration matrix, gloss, smoothness, thermal expansion performance, etc. of the glass composition cannot meet the standards. Therefore, the stability, mechanical strength, bonding strength with the restoration matrix, gloss, smoothness, thermal expansion performance and other indicators are adjusted by adding alkali metal oxides Na2O, K2O and Li2O. When alkali metal oxides are added, they will destroy the three-dimensional network structure of SiO2. Alkali metal ions (Na + , K + , Li + ) will enter the network structure of SiO2, breaking the silicon-oxygen bond (Si-O) and making the structure of the glass loose. For example, in a glass composition containing Na2O, Na + The ions will combine with the non-bridging oxygen in the SiO2 network, reducing the degree of polymerization of the network, so that the glass can be melted at a lower temperature. Alkali metal oxides Na2O, K2O and Li2O can also adjust the refractive index of the glass composition. Different alkali metal oxide contents will change the refractive index of the glass ceramic. The desired refractive index can be obtained by adjusting the type and content of alkali metal oxides. The ratio of the components of the present invention both promotes and inhibits the various properties of the enamel surface. It is not a simple superposition of effects, and each component is not the more the better, or the less the better, but only after precise regulation can the technical effects stated in the present invention be achieved.
[0031] Preferably, the average particle size D50 of the basic glass powder is 5 to 25 μm, for example, it can be 5 μm, 8 μm, 10 μm, 12 μm, 14 μm, 17 μm, 19 μm, 21 μm, 23 μm or 25 μm, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0032] Preferably, the volume proportion of particles below 2 μm in the basic glass powder to all particles is less than 5wt%, for example, it can be 1wt%, 1.8wt%, 2.6wt%, 3.4wt%, 4.2wt%, 4.9wt% or 5wt%, etc., but is not limited to the listed values, and other values not listed in this range are equally applicable, and / or, the volume proportion of particles above 40 μm in the basic glass powder to all particles is less than 25wt%, for example, it can be 1wt%, 2wt%, 4wt%, 7wt%, 10wt%, 12wt%, 15wt%, 18wt%, 23wt% or 25wt%, etc., but is not limited to the listed values, and other values not listed in this range are equally applicable.
[0033] The present invention controls the average particle size D50 of the basic glass powder within the above range. When the volume proportion of particles above 40 μm in all particles is too large, the glass composition may have a stress concentration problem. Defects are likely to occur inside larger particles or at the interface between particles. When the material is subjected to external force, these defective parts will become the starting points of cracks, and the cracks tend to expand rapidly in these relatively weak areas, resulting in reduced strength, hardness and wear resistance of the material; when the average particle size is large, the scattering of light is enhanced, which reduces the gloss of the glaze and makes it look duller. When the volume proportion of particles below 2 μm in all particles is too large, the glass particles agglomerate during paste formation, and the consistency sometimes changes.
[0034] Preferably, the glass composition further comprises a forming liquid, and the forming liquid comprises an organic solvent and an additive.
[0035] Preferably, the boiling point of the organic solvent is 150-400°C, for example, it can be 150°C, 178°C, 206°C, 234°C, 262°C, 289°C, 317°C, 345°C, 373°C or 400°C, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0036] Preferably, the refractive index of the organic solvent is greater than 1.45, for example, it can be 1.45, 1.49, 1.53, 1.57, 1.61, 1.65, 1.69, 1.73, 1.77 or 1.8, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0037] Preferably, the organic solvent comprises any one of 1,3-butanediol, glycerol, 1,5-pentanediol, triethylene glycol, dimethyl phthalate, diethyl phthalate, diethyl phthalate, polyethylene glycol, 2-phenoxyethanol or ethylene glycol phenyl ether, or a combination of at least two thereof, wherein a typical but non-limiting combination is a combination of 1,3-butanediol and glycerol, a combination of 1,5-pentanediol and glycerol, a combination of 1,3-butanediol and 1,5-pentanediol, a combination of triethylene glycol and glycerol, a combination of 1,3-butanediol and dimethyl phthalate, a combination of diethyl phthalate and glycerol, a combination of 2-phenoxyethanol and glycerol, preferably any one of 1,3-butanediol, polyethylene glycol, triethylene glycol or ethylene glycol phenyl ether, or a combination of at least two thereof, preferably containing 1,3-butanediol. The organic solvent is the main body of the molding liquid. The higher the refractive index of the organic solvent, the closer it is to the refractive index of the powder, and the more transparent the prepared paste. These organic solvents can be used alone or in combination of two or more. When two or more organic solvents are used in combination, the boiling point of each organic solvent used is multiplied by the addition ratio and the sum of the values is used.
[0038] Preferably, the mass ratio of 1,3-butanediol in the organic solvent to the forming liquid is 75-85wt%, for example, it can be 75wt%, 76wt%, 77wt%, 78wt%, 79wt%, 80wt%, 81wt%, 82wt%, 83wt%, 84wt% or 85wt%, etc.
[0039] Preferably, the content of the additive in the molding liquid is 0.1-10wt% by mass percentage, for example, it can be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 8wt%, 9wt% or 10wt%, etc.
[0040] Preferably, the additive comprises any one of a dispersant, a suspension stabilizer or a binder or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of a dispersant and a suspension stabilizer, a combination of a binder and a suspension stabilizer, and a combination of a dispersant and a binder.
[0041] Preferably, the additive comprises an inorganic salt, and the inorganic salt comprises any one or a combination of at least two of Sr salts, Zn salts, Ce salts, Na salts, Li salts or Ca salts, wherein typical but non-limiting combinations are a combination of Sr salts and Zn salts, a combination of Ce salts and Zn salts, a combination of Sr salts and Ce salts, and a combination of Na salts and Zn salts.
[0042] Preferably, the anions in the inorganic salt include any one of chloride, nitrate, sulfate or carbonate, or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of chloride and nitrate, a combination of sulfate and nitrate, a combination of chloride and sulfate, a combination of carbonate and nitrate, and a combination of chloride and carbonate.
[0043] Preferably, the additive may be a chloride, nitrate, sulfate, carbonate and / or hydrates thereof composed of an element selected from Sr, Zn, Ce, Na, Li, and Ca. More specific examples include strontium chloride, zinc chloride, cerium chloride, sodium chloride, lithium chloride, calcium chloride, strontium nitrate, zinc nitrate, cerium nitrate, sodium nitrate, lithium nitrate, calcium nitrate, strontium sulfate, zinc sulfate, cerium sulfate, sodium sulfate, lithium sulfate, calcium sulfate, strontium carbonate, zinc carbonate, cerium carbonate, sodium carbonate, lithium carbonate, calcium oxide and / or hydrates thereof.
[0044] In a second aspect, the present invention provides a method for preparing the basic glass powder in the paste-like dental glass composition described in the first aspect, the preparation method comprising: mixing, melting, cooling and crushing raw materials to obtain the basic glass powder.
[0045] Preferably, the melting temperature is 1250-1400°C, for example, it can be 1250°C, 1267°C, 1284°C, 1300°C, 1317°C, 1334°C, 1350°C, 1367°C, 1384°C or 1400°C, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0046] Preferably, the melting time is 1 to 5 h, for example, 1 h, 1.5 h, 1.9 h, 2.4 h, 2.8 h, 3.3 h, 3.7 h, 4.2 h, 4.6 h or 5 h, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0047] Preferably, the cooling includes: injecting the molten liquid into cold water at a flow rate controlling the diameter of the fluid column to be 0.1 to 8 mm for quenching, for example, it can be 0.1 mm, 0.2 mm, 0.5 mm, 0.8 mm, 1.0 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm or 8 mm, etc., and the preferred diameter is 2 to 5 mm.
[0048] The "average particle size D50" in the present invention is a median particle size (median diameter) indicating the average value of particles. The average particle size of the glass composition powder can be obtained by, for example, using a measurement method such as a laser diffraction scattering method, a dynamic light scattering method, a centrifugal sedimentation method, an electric sensitive area method, a sieving method, a photon correlation method, etc. In any measurement method, as long as the average particle size D50 of the glass composition powder of the present invention is 5 to 25 μm, for example, it can be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 12 μm, 13 μm, 15 μm, 18 μm, 20 μm, 22 μm or 25 μm.
[0049] As a preferred technical solution of the method of the present invention, the method for crushing the glass block is: the cooled glass block is crushed by air flow using an air flow crushing classifier (with a main engine frequency of 14 Hz) to obtain glass powder. Compared with crushing using a ball mill, this preferred technical solution is more efficient, easier to operate, and saves more time and manpower.
[0050] In a third aspect, the present invention provides a method for preparing the paste-like dental glass composition according to the first aspect, the preparation method comprising: mixing a forming liquid with a base glass powder and stirring the mixture under vacuum to obtain the glass composition;
[0051] Preferably, the powder-liquid mass ratio of the basic glass powder to the molding liquid is 0.4-0.7:1, for example, it can be 0.4:1, 0.45:1, 0.5:1, 0.55:1, 0.6:1, 0.65:1 or 0.7:1.
[0052] In a fourth aspect, the present invention provides a paste-like dental material, wherein the paste-like dental material is sintered and cooled using the paste-like dental glass composition described in the first aspect to obtain a paste-like dental material; the friction coefficient of the paste-like dental material is lower than 0.5, for example, it may be 0.49, 0.48, 0.47, 0.46, 0.45, 0.44, 0.42, 0.40, 0.41, 0.38, 0.35, 0.32 or 0.3, etc., but is not limited to the listed values, and other values not listed within the range are also applicable.
[0053] Preferably, the sintering temperature is 680-880°C, for example, it can be 680°C, 703°C, 725°C, 747°C, 769°C, 792°C, 814°C, 836°C, 858°C or 880°C, but is not limited to the listed values. Other unlisted values within this range are also applicable, preferably 700-760°C, and more preferably 700-720°C.
[0054] Preferably, the sintering holding time is 1 to 10 minutes, for example, 1 minute, 2 minutes, 3 minutes, 4 minutes, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes or 10 minutes, but is not limited to the listed values. Other unlisted values within the numerical range are also applicable, preferably 1-6 minutes, and more preferably 2-4 minutes.
[0055] Preferably, the sintering heating rate is 45-60°C / min, for example, it can be 45°C / min, 47°C / min, 49°C / min, 50°C / min, 52°C / min, 54°C / min, 55°C / min, 57°C / min, 59°C / min or 60°C / min, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0056] Preferably, preheating is performed before sintering.
[0057] Preferably, the preheating temperature is 400-500°C, for example, it can be 400°C, 412°C, 423°C, 434°C, 445°C, 456°C, 467°C, 478°C, 489°C or 500°C, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0058] Preferably, the preheating time is 1 to 4 minutes, for example, it can be 1 minute, 1.4 minutes, 1.7 minutes, 2 minutes, 2.4 minutes, 2.7 minutes, 3 minutes, 3.4 minutes, 3.7 minutes or 4 minutes, but is not limited to the listed values, and other values not listed within the range are also applicable.
[0059] Preferably, the strength of the paste-like dental material is greater than 150 MPa, for example, it can be 150 MPa, 156 MPa, 162 MPa, 167 MPa, 173 MPa, 178 MPa, 184 MPa, 189 MPa, 195 MPa or 200 MPa, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0060] Preferably, the paste-like dental material is translucent.
[0061] Compared with the prior art, the present invention has at least the following beneficial effects:
[0062] (1) The paste-like dental material provided by the present invention improves the wear resistance by optimizing the components and ratio of the basic glass powder in the glass composition, while reducing the melting temperature of the glass composition and shortening the time required for sintering, thereby greatly reducing energy consumption and costs for industrial production and broadening the application range of the glass composition, so that the glass composition can be applied to not only zirconia restoration substrates with high melting temperatures, but also glass ceramics, cast porcelain and other restoration substrates with low melting temperatures;
[0063] (2) The forming liquid of the paste-like dental glass composition provided by the present invention uses an organic solvent with a refractive index greater than 1.45, which is close to the refractive index of the powder, and the prepared paste has higher transparency and is translucent; and by optimizing the components and ratio of the forming liquid, the solvent is more easily volatilized during the sintering process, avoiding the problem of blackening of the glaze surface caused by solvent residue; by optimizing the average particle size and particle size distribution range of the glass composition powder and the dilution ratio of the forming liquid, the glaze surface after sintering can be made more uniform and smoother, thereby improving the quality of the glaze surface after sintering;
[0064] (3) Under preferred conditions, the paste-like dental glass composition provided by the present invention has a friction coefficient of less than 0.5, a softening point of 560°C, a three-point bending strength of more than 160 MPa, and a thermal expansion coefficient of 8.5×10 -6 / K, the appropriate firing temperature is low, only 680°C, and there are no bubbles after firing, the color is not gray or black, and it can meet the requirements of stability, mechanical strength, bonding strength with the restoration matrix, gloss, smoothness, thermal expansion performance, etc. DETAILED DESCRIPTION
[0065] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0066] Example 1
[0067] The present embodiment provides a paste-like basic dental glass powder, wherein the average particle size D50 of the paste-like basic dental glass powder is 15 μm; the volume proportion of particles below 2 μm in the basic glass powder among all particles is 3.5 wt %, and the volume proportion of particles above 40 μm in the basic glass powder among all particles is 10 wt %.
[0068] The present embodiment also provides a method for preparing the paste-like basic dental glass powder, which comprises: mixing raw materials (in terms of mass fraction, the raw materials include SiO2: 55%, B2O3: 14%, Na2O: 9%, K2O: 9%, Li2O: 1%, CaO: 3%, alumina with an average particle size D50 of 20 nm: 8%, yttrium oxide with an average particle size D50 of 40 nm: 1%, and alumina / yttrium oxide mass ratio of 8:1) for 30 minutes, melting the obtained mixture at high temperature, using a platinum crucible for melting, melting at 1400°C for 4 hours, injecting the molten liquid into cold water at a flow rate of 3.5 mm to quench the molten liquid, crushing the molten liquid after quenching to obtain particles with a longest diameter of less than 15 mm, and refining the obtained particles into fine powder using an airflow milling process, and performing airflow milling. The corresponding parameters of the airflow milling are: a host frequency of 14 Hz, to obtain the basic glass powder.
[0069] Example 2
[0070] The present embodiment provides a paste-like basic dental glass powder, wherein the average particle size D50 of the paste-like basic dental glass powder is 25 μm; the volume proportion of particles below 2 μm in the basic glass powder among all particles is 2.7 wt %, and the volume proportion of particles above 40 μm in the basic glass powder among all particles is 24.3 wt %.
[0071] The present embodiment also provides a method for preparing the paste-like basic dental glass powder, which comprises: mixing raw materials (in terms of mass fraction, the raw materials include SiO2: 44%, B2O3: 15%, Na2O: 12%, K2O: 8%, Li2O: 3%, CaO: 5%, alumina with an average particle size D50 of 40 nm: 11%, yttrium oxide with an average particle size D50 of 30 nm: 2%, and alumina / yttrium oxide mass ratio of 5.5:1) for 35 minutes, melting the obtained mixture at high temperature, using a platinum crucible for melting, melting at 1350°C for 2 hours, injecting the molten liquid into cold water at a flow rate of 2 mm to control the diameter of the fluid column for quenching, crushing after quenching to obtain particles with a longest diameter of less than 15 mm, and using an airflow crushing process to refine the obtained particles into fine powder, and performing airflow crushing, and the corresponding parameters of the airflow crushing are: a host frequency of 14 Hz, to obtain the basic glass powder.
[0072] Example 3
[0073] The present embodiment provides a paste-like basic dental glass powder, wherein the average particle size D50 of the paste-like basic dental glass powder is 5 μm; the volume proportion of particles below 2 μm in the basic glass powder among all particles is 3.6 wt %, and the volume proportion of particles above 40 μm in the basic glass powder among all particles is 0.3 wt %.
[0074] The present embodiment also provides a preparation method of the paste-like basic dental glass powder, which comprises: mixing raw materials (in terms of mass fraction, the raw materials include SiO2: 60%, B2O3: 9.4%, Na2O: 10%, K2O: 6%, Li2O: 2.1%, CaO: 2%, alumina with an average particle size D50 of 10 nm: 10%, yttrium oxide with an average particle size D50 of 30 nm: 0.5%, and alumina / yttrium oxide mass ratio of 20:1) for 40 minutes, melting the obtained mixture at high temperature, using a platinum crucible for melting, melting at 1250°C for 5 hours, injecting the molten liquid into cold water at a flow rate of 5 mm to control the diameter of the fluid column for cold quenching, crushing after cold quenching to obtain particles with a longest diameter of less than 15 mm, and using an airflow milling process to refine the obtained particles into fine powder, and performing airflow milling, and the corresponding parameters of the airflow milling are: a host frequency of 14 Hz, to obtain the basic glass powder.
[0075] Example 4
[0076] The present embodiment provides a paste-like basic dental glass powder, wherein the average particle size D50 of the paste-like basic dental glass powder is 20 μm; the volume proportion of particles below 2 μm in the basic glass powder among all particles is 4.2 wt %, and the volume proportion of particles above 40 μm in the basic glass powder among all particles is 22.6 wt %.
[0077] The present embodiment also provides a preparation method of the paste-like basic dental glass powder, which comprises: mixing raw materials (in terms of mass fraction, the raw materials include SiO2: 59.4%, B2O3: 6%, Na2O: 12.35%, K2O: 9%, Li2O: 3%, CaO: 4.5%, alumina with an average particle size D50 of 20 nm: 5.5%, yttrium oxide with an average particle size D50 of 50 nm: 0.25%, and alumina / yttrium oxide mass ratio of 22:1) for 25 minutes, melting the obtained mixture at high temperature, using a platinum crucible for melting, melting at 1400°C for 1 hour, injecting the molten liquid into cold water at a flow rate of 3 mm to control the diameter of the fluid column for cold quenching, crushing after cold quenching to obtain particles with a longest diameter of less than 15 mm, and using an airflow crushing process to refine the obtained particles into fine powder, and performing airflow crushing, and the corresponding parameters of the airflow crushing are: a host frequency of 14 Hz, to obtain the basic glass powder.
[0078] Example 5
[0079] The present embodiment provides a paste-like basic glass powder for dental use. The basic glass powder is the same as that in Embodiment 1 except that the yttrium oxide content is adjusted to 0.5% and the SiO2 content is adjusted accordingly so that the mass ratio of aluminum oxide to yttrium oxide is 16:1. Such details will not be described again.
[0080] Example 6
[0081] The present embodiment provides a paste-like basic glass powder for dental use. The basic glass powder is the same as that in Embodiment 1 except that the yttrium oxide content is adjusted to 1.5% and the SiO2 content is adjusted accordingly so that the mass ratio of aluminum oxide to yttrium oxide is 5.33:1. Such details will not be repeated here.
[0082] Example 7
[0083] The present embodiment provides a paste-like basic glass powder for dental use. The basic glass powder is the same as that in Embodiment 1 except that the yttrium oxide content is adjusted to 2% and the SiO2 content is adjusted accordingly so that the mass ratio of aluminum oxide to yttrium oxide is 4:1. Such details will not be repeated here.
[0084] Example 8
[0085] This embodiment provides a paste-like basic glass powder for dental use. The basic glass powder is the same as that of Embodiment 1 except that CaO is not added and the contents of other components are adjusted in proportion accordingly, and will not be described again.
[0086] Example 9
[0087] The present embodiment provides a paste-like basic glass powder for dental use. The basic glass powder is the same as that of Embodiment 1 except that Li2O is not added and the contents of other components are adjusted in proportion accordingly, and details are not repeated here.
[0088] Example 10
[0089] The present embodiment provides a paste-like basic glass powder for dental use. The basic glass powder is the same as that of Embodiment 1 except that K2O is not added and the contents of other components are adjusted in proportion accordingly, and details are not repeated here.
[0090] Embodiment 11
[0091] The present embodiment provides a paste-like basic glass powder for dental use. The basic glass powder is the same as that of Embodiment 1 except that Na2O is not added and the contents of other components are adjusted in proportion accordingly, and details thereof will not be repeated here.
[0092] Example 12
[0093] The present embodiment provides a paste-like basic glass powder for dental use. The basic glass powder is the same as that of Embodiment 1 except that B2O3 is not added and the contents of other components are adjusted in proportion accordingly, and details are not repeated here.
[0094] Example 13
[0095] This embodiment provides a paste-like basic dental glass powder, which is the same as that of Embodiment 1 except that cold water is injected into the basic glass powder at a flow rate of 10 mm to control the diameter of the fluid column during quenching.
[0096] Comparative Example 1
[0097] This comparative example provides a paste-like basic glass powder for dental use. The basic glass powder is the same as Example 1 except that the yttrium oxide content is adjusted to 0.2% and the SiO2 content is adjusted accordingly so that the aluminum oxide / yttrium oxide mass ratio is 50:1.
[0098] Comparative Example 2
[0099] This comparative example provides a paste-like basic glass powder for dental use. The basic glass powder is the same as Example 1 except that the yttrium oxide content is adjusted to 2.5% and the SiO2 content is adjusted accordingly so that the aluminum oxide / yttrium oxide mass ratio is 2.5:1.
[0100] Comparative Example 3
[0101] This comparative example provides a paste-like basic dental glass powder, which is the same as Example 1 except that the aluminum oxide in the raw material is adjusted to have an average particle size D50 of 30 μm.
[0102] Comparative Example 4
[0103] This comparative example provides a paste-like basic dental glass powder, which is the same as Example 1 except that the yttrium oxide in the raw material is adjusted to have an average particle size D50 of 50 μm.
[0104] The particle size distribution of the basic glass powder in Examples 5 to 13 and Comparative Examples 1 to 4 is shown in Table 1.
[0105] Table 1
[0106]
[0107]
[0108] Application Example 1
[0109] This application example provides a paste-like dental glass composition, which includes the paste-like dental basic glass powder provided in Example 1 and a molding liquid. The mass ratio of the molding liquid to the basic glass powder is 0.6:1.
[0110] Calculated by mass fraction, the molding liquid includes 80% of 1,3-butanediol, 15% of polyethylene glycol 600, 4% of ethylene glycol phenyl ether, and 1% of strontium chloride.
[0111] This application example also provides a paste-like dental material, and a method for preparing the paste-like dental material. The preparation method comprises: preheating the above-mentioned paste-like dental glass composition at 450°C for 2 minutes to allow the solvent to evaporate fully to obtain a semi-finished product, and then heating the semi-finished product to 720°C at a heating rate of 60°C / min, maintaining for 2 minutes, and cooling to obtain a paste-like dental material (i.e., tooth enamel surface).
[0112] Application Example 2
[0113] This application example provides a paste-like dental glass composition, which includes the paste-like dental basic glass powder provided in Example 1 and a molding liquid. The mass ratio of the molding liquid to the basic glass powder is 0.4:1.
[0114] Calculated by mass fraction, the molding liquid includes 80% of 1,3-butanediol, 15% of polyethylene glycol 200, 3.5% of ethylene glycol phenyl ether, and 1.5% of strontium chloride.
[0115] This application example also provides a paste-like dental material, and a method for preparing the paste-like dental material. The preparation method comprises: preheating the above-mentioned paste-like dental glass composition at 400°C for 4 minutes to fully evaporate the solvent to obtain a semi-finished product, and then heating the semi-finished product to 730°C at a heating rate of 50°C / min, maintaining for 1.5 minutes, and cooling to obtain a paste-like dental material (i.e., tooth enamel surface).
[0116] Application Example 3
[0117] This application example provides a paste-like dental glass composition, which includes the paste-like dental basic glass powder provided in Example 1 and a molding liquid. The mass ratio of the molding liquid to the basic glass powder is 0.7:1.
[0118] Calculated by mass, the molding liquid includes 85% of 1,3-butanediol, 9.5% of polyethylene glycol 600, 5% of polyethylene glycol 200, and 0.5% of calcium chloride.
[0119] This application example also provides a paste-like dental material, and a method for preparing the paste-like dental material. The preparation method comprises: preheating the above-mentioned paste-like dental glass composition at 500°C for 1 minute to allow the solvent to evaporate fully to obtain a semi-finished product, then heating the semi-finished product to 710°C at a heating rate of 45°C / min, maintaining for 10 minutes, and cooling to obtain a paste-like dental material (i.e., tooth enamel surface).
[0120] Application Example 4
[0121] This application example provides a paste-like dental glass composition, which includes the paste-like dental basic glass powder provided in Example 1 and a molding liquid. The mass ratio of the molding liquid to the basic glass powder is 0.5:1.
[0122] Calculated by mass fraction, the molding liquid includes 80% of 1,3-butanediol, 13.8% of triethylene glycol, 5% of ethylene glycol phenyl ether, and 1.2% of calcium chloride.
[0123] This application example also provides a paste-like dental material, and a method for preparing the paste-like dental material. The preparation method comprises: preheating the above-mentioned paste-like dental glass composition at 420°C for 3 minutes to fully evaporate the solvent to obtain a semi-finished product, and then heating the semi-finished product to 720°C at a heating rate of 48°C / min, maintaining for 2 minutes, and cooling to obtain a paste-like dental material (i.e., tooth enamel surface).
[0124] Application Examples 5 to 13 and Comparative Application Examples 1 to 4
[0125] Application Examples 5 to 13 and Application Comparative Examples 1 to 4 provide a paste-like dental glass composition. Except for using the basic glass powder in Examples 5 to 13 and Comparative Examples 1 to 4, the rest of the paste-like dental glass composition is the same as Application Example 1, which will not be repeated here.
[0126] Application Example 14
[0127] This application example provides a paste-like dental glass composition, which is the same as Application Example 1 except that strontium chloride is not added to the molding liquid and is completely replaced by 1,3-butanediol.
[0128] Application Example 15
[0129] This application example provides a paste-like dental glass composition, which is the same as that of Application Example 1 except that all strontium chloride in the molding liquid is replaced by sodium chlorate.
[0130] Application Example 16
[0131] This application example provides a paste-like dental glass composition, which is the same as that of Application Example 1 except that strontium chloride in the molding liquid is completely replaced by sodium pyrophosphate.
[0132] Application Example 17
[0133] This application example provides a paste-like dental glass composition, which is the same as that of Application Example 1 except that all organic matter in the molding liquid is replaced with 1,5-pentanediol.
[0134] Application Example 18
[0135] This application example provides a paste-like dental glass composition, which is the same as that of Application Example 1 except that all organic matter in the molding liquid is replaced with dimethyl phthalate.
[0136] Application Example 19
[0137] This application example provides a paste-like dental glass composition, which is the same as that of Application Example 1 except that all organic matter in the molding liquid is replaced with glycerol.
[0138] Application Example 20
[0139] This application example provides a paste-like dental glass composition, which is the same as that of Application Example 1 except that the mass ratio of the forming liquid to the base glass powder is 1.2:1.
[0140] Application Example 21
[0141] This application example provides a paste-like dental glass composition, which is the same as that of Application Example 1 except that the mass ratio of the forming liquid to the base glass powder is 0.2:1.
[0142] Test method: The average particle size D50 and the maximum particle size D100 of the substrate glass can be determined by using laser diffraction scattering, dynamic light scattering, centrifugal sedimentation, electric sensitive area method, sieving method, photon correlation method, etc. The particle size of the glass powder of the example was measured by laser diffraction scattering.
[0143] Whether the base glass has crystals can be confirmed by measurement using an X-ray diffraction apparatus.
[0144] Determination of thermal expansion coefficient and softening point: knead each substrate glass with distilled water, fill the kneaded product in a silicon rod-shaped mold (5×5×25mm), repeatedly concentrate and absorb water to prepare a molded body. Take out the molded body from the silicon mold, use a dental technician ceramic firing furnace to perform vacuum firing once and atmospheric firing once, a total of two times. Grind the two ends of the obtained secondary fired product into parallel surfaces, and adjust the size of the sample to (5±0.2)×(5±0.2)×(25±0.2)mm as a test sample, and use a thermal dilatometer to determine the thermal expansion coefficient and softening point according to the steps in GB30367.
[0145] Determination of bending strength: knead each substrate glass with distilled water, fill the kneaded product in a silicon rod-shaped mold (3×6×25mm), repeatedly concentrate and absorb water to prepare a molded body. Take out the molded body from the silicon mold, vacuum sinter it using a dental ceramic sintering furnace, and prepare 10 sintered products. Grind the entire surface of the obtained sintered product into parallel surfaces, and adjust the size of the sample to (1.5±0.2)×(4±0.2)×(18±0.2)mm as a test sample. According to the steps in GB30367, use a universal testing machine to measure the bending strength.
[0146] Friction performance: The prepared paste-like dental glass composition was sintered on a zirconia tooth. After sintering, the sample was subjected to a friction and wear test using a multifunctional friction and wear testing machine. A reciprocating sliding friction and wear test was performed on the sample surface, and the friction coefficient of the sample surface was recorded after 100,000 cycles.
[0147] The test results of the above application examples and application comparison examples are shown in Table 2.
[0148] Table 2
[0149]
[0150]
[0151] From Table 1, we can see the following points:
[0152] (1) Comprehensive application examples 1 to 4 show that the paste-like dental glass composition provided by the present invention has a friction coefficient of less than 0.45, a softening point of 560°C, a three-point bending strength of more than 160 MPa, and a thermal expansion coefficient of 8.5×10 -6 / K, the appropriate firing temperature is low, only 680℃, and there are no bubbles after firing, and the color does not turn gray or black, which can meet the clinical needs of oral restoration and achieve the need to match the tribological properties of dental ceramics with human enamel;
[0153] (2) It can be seen from the comprehensive application example 1 and application examples 5 to 7 that the mass ratios of aluminum oxide / yttrium oxide in application examples 5 to 7 are 16:1, 5.33:1, and 4:1, respectively. In application example 1, the friction coefficient is only 0.41, and the three-point bending strength is as high as 166.3 MPa, while the friction coefficient in application example 5 is 0.47, and the wear resistance is not as good as that in application example 1. The bending strength in application examples 6 to 7 decreases to 158.3 MPa and 157.4 MPa, respectively. This shows that the present invention can better improve the comprehensive performance of the paste-like dental material by controlling the mass ratio of aluminum oxide / yttrium oxide within a reasonable range.
[0154] (3) It can be seen from the combined application examples 1 and 8 that calcium oxide is not added in application example 8, the friction coefficient is 0.55, the wear resistance is not as good as that in application example 1, and the bending strength is reduced to 120.8 MPa. This shows that the present invention can significantly improve the wear resistance and bending strength of the paste-like dental material by combining calcium oxide with aluminum oxide / yttrium oxide.
[0155] (4) It can be seen from Application Example 1 and Application Examples 9 to 12 that the paste-like dental material of the present invention can achieve high flexural strength and high wear resistance, which is not only dependent on the combination of aluminum oxide and yttrium oxide. The basic system components to which aluminum oxide and yttrium oxide are added are also critical. The lack of any one of them will lead to reduced flexural strength and wear resistance.
[0156] (5) It can be seen from the combined application example 1 and the application example comparative examples 1-2 that the glass compositions provided in comparative examples 1-2 have a wear resistance coefficient of the paste-like dental material of above 0.50, which is significantly lower than that in application example 1. This indicates that the doping amount of yttrium oxide and its mass ratio with aluminum oxide are critical to improving the wear resistance coefficient of the paste-like dental material.
[0157] (6) It can be seen from the combined application example 1 and the comparative examples 3 to 4 that the yttrium oxide and aluminum oxide in the comparative examples 3 to 4 use micron-grade raw materials, resulting in a wear resistance coefficient of the paste-like dental material being above 0.50, which is significantly lower than that in the application example 1. This indicates that the use of nano-grade yttrium oxide and nano-grade aluminum oxide as raw materials in the present invention is critical to improving the wear resistance and flexural strength of the final paste-like dental material.
[0158] (7) It can be seen from Application Example 1 and Application Example 13 that the particle size distribution of the basic glass powder also has a great influence on the improvement of the wear resistance and bending strength of the paste-like dental material. The present invention preferably adopts an appropriate particle size range to obtain a basic glass powder with a more suitable particle size.
[0159] (8) It can be seen from the combined application example 1 and application examples 14 to 16 that in application example 14, since strontium chloride was not added as an additive, a large consistency change occurred, resulting in the generation of bubbles during the firing process; sodium chlorate was used in application example 15, and the final wear resistance was lower than that of application example 1; sodium pyrophosphate was used in application example 16, which was difficult to achieve the effect of an additive and still produced a large consistency change, and bubbles were generated during the final firing process. This shows that the present invention can further reduce the generation of bubbles during the firing process by using inorganic salts as additives.
[0160] (9) It can be seen from Application Example 1 and Application Examples 17 to 19 that the combined use of organic substances can significantly reduce the generation of bubbles during the firing process. However, the pastes in Application Examples 17 and 19 are no longer clear after sintering, and sedimentation and blackening of the coating surface occur.
[0161] (10) It can be seen from Application Example 1 and Application Examples 20 to 21 that the paste-like dental glass composition provided by the present invention can better improve the three-point bending strength and avoid the generation of bubbles during firing by controlling the mass ratio of the molding liquid to the base glass powder within a reasonable range.
[0162] The present invention illustrates the detailed features of the present invention through the above embodiments, but the present invention is not limited to the above detailed features, that is, it does not mean that the present invention must rely on the above detailed features to be implemented. Those skilled in the art should understand that any improvement to the present invention, equivalent replacement of the technical features selected by the present invention, addition of auxiliary technical features, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A paste-like dental glass composition, characterized in that: The glass composition comprises a basic glass powder and a forming liquid, wherein the basic glass powder comprises aluminum oxide and yttrium oxide; Wherein, the mass ratio of aluminum oxide to yttrium oxide is 2.75-44:
1.
2. The glass composition according to claim 1, characterized in that The aluminum oxide raw material and the yttrium oxide raw material in the basic glass powder are independently nano aluminum oxide and nano yttrium oxide.
3. The glass composition according to claim 1, characterized in that According to mass fraction, the composition of the basic glass powder is as follows: Preferably, the alkali metal oxide comprises a combination of Na2O, K2O and Li2O; Preferably, the content of Na2O in the basic glass powder is 3-14% by mass fraction; Preferably, the content of K2O in the basic glass powder is 4-10% by mass; Preferably, the content of Li2O in the basic glass powder is 0.5-3% by mass.
4. The glass composition according to claim 3, characterized in that The average particle size D50 of the basic glass powder is 5 to 25 μm; Preferably, the volume proportion of particles below 2 μm in the base glass powder is below 5 wt % of all particles, and / or the volume proportion of particles above 40 μm in the base glass powder is below 25 wt % of all particles.
5. The glass composition according to claim 1, characterized in that The molding liquid includes an organic solvent and an additive; Preferably, the boiling point of the organic solvent is 150-400°C; Preferably, the refractive index of the organic solvent is greater than 1.45; Preferably, the organic solvent includes at least 1,3-butanediol; Preferably, the content of the additive in the molding liquid is 0.1 to 10 wt % by mass percentage; Preferably, the additive comprises an inorganic salt, and the inorganic salt comprises any one or a combination of at least two of Sr salt, Zn salt, Ce salt, Na salt, Li salt or Ca salt; Preferably, the anions in the inorganic salt include any one of chloride, nitrate, sulfate or carbonate, or a combination of at least two thereof.
6. A method for preparing a basic glass powder in a paste-like dental glass composition according to any one of claims 1 to 5, characterized in that: The preparation method comprises: mixing, melting, cooling and crushing raw materials to obtain the basic glass powder; Preferably, the melting temperature is 1250-1400°C; Preferably, the melting time is 1 to 5 hours; Preferably, the cooling comprises: injecting the molten liquid into cold water for quenching at a flow rate controlling the diameter of the fluid column to be 0.1 to 8 mm, preferably with a diameter of 2 to 5 mm.
7. A method for preparing the paste-like dental glass composition according to any one of claims 1 to 5, characterized in that: The preparation method comprises: mixing the forming liquid with the basic glass powder and stirring the mixture under vacuum to obtain the glass composition; Preferably, the powder-liquid mass ratio of the basic glass powder to the molding liquid is 0.4-0.7:
1.
8. A dental paste material, obtained by sintering and cooling the dental paste glass composition according to any one of claims 1 to 5, characterized in that: The paste-like dental material has a friction coefficient lower than 0.5.